Islamic Law Study of Persuasive Communication After The Occurrence Of Polygamy in Kauman Society - Ibrahim, Malik; Al Mamun, Abdullah; Jarong, Koree; Bouaoune, Djihad; Mubarrok, Muhammad Agus Wahid; Ramadhonah, Indah Siti; Dharojah, Rakhma Widya (Program Studi Hukum Keluarga Islam, 2024)
Polygamy is one of the actions that many men even desire even though many women refuse to be polygamous, but there are also some women who are willing to be polygamous with certain guarantees and conditions. Polygamy is very influential in the division of the household, this problem can be solved by using persuasive communication even though this is not the main factor to increase the harmonious family after polygamy. This study aims to analyse what efforts are made by married couples in re-improving family harmony after disputes due to polygamy, what models and principles of persuasive communication are used by husbands in persuading wives after quarrels due to polygamy. This research uses descriptive qualitative research. This research uses data collection techniques of observation, interviews, and documentation. Data analysis techniques use data reduction and conclusion drawing, and data validity with triangulation. The results of the study show that efforts to improve family harmony after polygamy can be done by persuading and convincing the wife, making a stamped agreement letter to divorce the second wife, asking for prayer and guidance from a kyai, and a husband arguing how his children will fare when fighting and divorcing. In the persuasive communication model, a husband uses probabilogical persuasiveness, and in the principle of persuasive communication, a husband uses the principle of hope.